Structural Analysis of the Victoria Quadrangle Fault Systems on Mercury: Timing, Geometries, Kinematics, and Relationship with the High‐Mg Region. Issue 10 (16th October 2019) - Galluzzi, V.; Ferranti, L.; Massironi, M.; Giacomini, L.; Guzzetta, L.; Palumbo, P.
Abstract: Three nonparallel fault systems occur in the Victoria quadrangle of Mercury. The most prominent system (Victoria system) includes the NNW‐SSE trending Victoria Rupes‐Endeavour Rupes‐Antoniadi Dorsum (VEA) array, one of the major fault alignments on the planet, and shorter parallel fault arrays. West and northwest of the Victoria system, two additional fault systems with NE‐SW (Larrocha system) and NW‐SE (Carnegie system) trends, are found. The timing analysis reveals that the three systems are coeval and were active until ~3.7 Ga. Measures of rim offset within faulted craters on the VEA array and on Carnegie Rupes segment of the Carnegie system were used to derive the kinematics of faults and to perform a finite stress inversion, which provides an ENE‐WSW trending regional shortening axis. Results of the stress inversion and age relationships, together with geometrical and morpho‐structural observations, suggest that the NE‐SW and NW‐SE systems acted as right‐transcurrent and left‐transpressional, respectively, at the time when the computed strain field was active. The distribution of the three systems spatially coincides with the boundaries of the high‐Mg region and of other regional geochemical terranes. Lateral geomechanical variation of the crust combined with tidal despinning and global contraction processes drove the localization and slip pattern of faults in a kinematically consistent displacement field. Moreover, crustal heterogeneities controlled the lateral changes in density and spacing of fault segments along the VEA. Following the demise of faulting, the established lateral variation of geometry along the VEA favored the growth of volcanic vents at high‐permeability segment boundaries. Plain Language Summary: Thanks to the recent completion of the geological map of a wide region of Mercury, named Victoria quadrangle, we observe three main orientations of scarps, which are the surface expressions of fault systems. We find out that the three fault systems formed before 3.7 Ga ago and that the principal force that created these systems had a main WNW‐ESE direction. This shortening force should have caused pure compression on the systems perpendicular to its direction and oblique to lateral movements on the rest of the faults, although global tectonic models proposed for Mercury do not expect this deformation scenario in this area. However, we observe that the systems are preferentially located in distinct areas of the quadrangle. They are found within and around a peculiar crustal high‐density region with high‐magnesium abundance possibly characterized by a high‐magma production in the past. We conclude that its activity and density influenced the geometry of faults and their deformation style. Our findings suggest that lateral compositional variations of the crust should be taken into consideration when dealing with global tectonic models of Mercury. Key Points: The Victoria quadrangle of Mercury encompasses three coeval fault systems The three systems were formed by a nonisotropic stress field Fault nucleation was controlled by preexisting crustal heterogeneities